Comparison of Various Glucocorticoid Replacement Regimens Used in Chronic Adrenal Insufficiency: A Systematic Review - Kiko, Nduku; Kalhan, Atul (Dubai Diabetes and Endocrinology Journal, 2020)
Objective: Patients with adrenal insufficiency require life-long glucocorticoid replacement therapy. Hydrocortisone (15–30 mg/day) and prednisolone (3–7.5 mg/day) are the preferred agents used although there is a lack of consensus among endocrinologists regarding the impact of different steroid regimens on quality of life, bone metabolism, cardiometabolic outcomes, adrenal crisis and infections. We carried out a retrospective systematic review of the literature to compare the efficacy and side effects of various glucocorticoid replacement regimens in patients with chronic adrenal insufficiency. Methods: We searched PubMed, Cochrane Reviews and Google Scholar databases up to March 14, 2019, for studies evaluating various clinical outcomes with glucocorticoid replacement therapy. The abstracts and full studies were appraised and data extracted from the eligible studies. The quality of evidence was evaluated and risk of bias carried out. Results: A total of 47 studies including 9 randomised controlled trials (RCTs) and 38 observational studies were evaluated in this systematic review. Prednisolone therapy was observed to be safe as well as efficacious as hydrocortisone although a higher dose was associated with an increased risk of cardiovascular (CV) disease. A lower hydrocortisone dose (15–20 mg/day) was associated with a reduction of blood pressure and improved clinical outcomes although this observation was based on a solitary RCT. Modified release hydrocortisone was observed to reduce the risk of CV disease based upon results from 2 of the RCTs. However, there was no conclusive evidence of benefit of modified release hydrocortisone and continuous subcutaneous hydrocortisone infusion in improving subjective health status. Conclusion: Prednisolone therapy remains a safe and efficacious alternative to hydrocortisone although there are concerns of dyslipidaemia and CV disease with higher doses. There is limited level I evidence suggestive of a positive effect of modified release hydrocortisone on CV and metabolic outcomes, particularly weight reduction.